2020
DOI: 10.1002/adhm.201901373
|View full text |Cite
|
Sign up to set email alerts
|

Maladaptive Contractility of 3D Human Cardiac Microtissues to Mechanical Nonuniformity

Abstract: Cardiac tissues are able to adjust their contractile behavior to adapt to the local mechanical environment. Nonuniformity of the native tissue mechanical properties contributes to the development of heart dysfunctions, yet the current in vitro cardiac tissue models often fail to recapitulate the mechanical nonuniformity. To address this issue, a 3D cardiac microtissue model is developed with engineered mechanical nonuniformity, enabled by 3D‐printed hybrid matrices composed of fibers with different diameters. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
(55 reference statements)
0
10
0
Order By: Relevance
“…Many technologies are being developed, including self-assembled spheroids/organoids 6 , 44 46 , organ-on-a-chip 47 , 48 , and microtissue platforms 42 , 43 , 49 . In addition, to better mimic cardiac disease, pathological features are being introduced using hypoxia-induced apoptosis 6 , mechanical stress 50 , or varied cardiac cell ratios 51 . Recent examples have also demonstrated that the introduction of electrical barriers such as holes in healthy cardiac tissue or fibroblast dense regions disrupts action potential propagation 46 , 52 .…”
Section: Resultsmentioning
confidence: 99%
“…Many technologies are being developed, including self-assembled spheroids/organoids 6 , 44 46 , organ-on-a-chip 47 , 48 , and microtissue platforms 42 , 43 , 49 . In addition, to better mimic cardiac disease, pathological features are being introduced using hypoxia-induced apoptosis 6 , mechanical stress 50 , or varied cardiac cell ratios 51 . Recent examples have also demonstrated that the introduction of electrical barriers such as holes in healthy cardiac tissue or fibroblast dense regions disrupts action potential propagation 46 , 52 .…”
Section: Resultsmentioning
confidence: 99%
“…Due to increased contractile force, severe contractile inefficiency was induced through prolonged force release. 43 Mechanical loading also plays an important role in disease progression in hypertrophic cardiomyopathy and dilated cardiomyopathies. Isogenic homozygous myosin-binding protein C cardiac isoform (MYBPC3) hiPSC cell line results in loss of function in MYBPC3 protein in sarcomere A-bands leading to dysfunction of contractility.…”
Section: Mechanical Loadingmentioning
confidence: 99%
“…A matrix with alternating thick and thin filament sections further increased the time intervals between beats, suggesting impaired transition between contraction and relaxation function. Due to increased contractile force, severe contractile inefficiency was induced through prolonged force release 43 …”
Section: Disease Modelsmentioning
confidence: 99%
“… 151 By quantifying the deflection of fibers under cell-generated stresses, the non-uniformity of microenvironmental properties leads to contractile malfunction and disorganization in myocardial tissues. 195 A fibronectin-derived grid can also be used in a similar fashion draped on top of individual cells, cell sheets, or tissues, where the grid deformations provide reference-free compression and tension quantification. 196 …”
Section: Measuring Forces At the Tissue Length Scalementioning
confidence: 99%